2023
DOI: 10.1039/d3ja00012e
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the digestion capability of ammonium bifluoride for the determination of major and trace elements in Ti-rich minerals by ICP-MS

Abstract: Complete sample digestion is a prerequisite to achieve accurate and precise results of elemental concentrations and isotopic compositions in Ti-bearing minerals of interest, such as refractory rutile. In this study,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The titanium mineral present in the ore under study might be ilmenite or rutile. Liu et al 17 have shown that extended digestion of the mineral with ABF for more than 4 hours at 230 °C recovers Ti completely in rutile. However, for processing a large number of samples, rapid digestion and dissolution were required.…”
Section: Optimization Of Temperature and Duration Of Digestionmentioning
confidence: 99%
See 1 more Smart Citation
“…The titanium mineral present in the ore under study might be ilmenite or rutile. Liu et al 17 have shown that extended digestion of the mineral with ABF for more than 4 hours at 230 °C recovers Ti completely in rutile. However, for processing a large number of samples, rapid digestion and dissolution were required.…”
Section: Optimization Of Temperature and Duration Of Digestionmentioning
confidence: 99%
“…Zhang et al 15 demonstrated that ABF can be effectively used for digestion in open and closed vessel processes. ABF has already been applied to various refractory mineral bearing ores such as Nb–Ta rich (coltan) ores, 16 rutile, ilmenite, and perovskite Ti-rich minerals; 17 post-detonation nuclear forensic analysis; 18 trinitrite samples; 19 forensic nuclear debris; 20 zircon; 21 and scheelite. 22 However, ABF can only decompose silicate-bound tin 23 in geological rock samples, whereas mineral cassiterite remains unattacked by any acid or the combination of HF–HNO 3 /HCl–HClO 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Rapid and simple digestion procedures that achieve total dissolution remain a priority. Liu et al 191 evaluated the ability of ammonium bifluoride (NH 4 HF 2 ) to digest Ti-rich minerals such as rutile, ilmenite, titanite and perovskite for the determination of major and trace elements by ICP-MS. Complete digestion of 50 mg samples was achieved in 4 h using 300 mg of NH 4 HF 2 at 230 °C.…”
Section: Analysis Of Geological Materialsmentioning
confidence: 99%
“…Recently, Hu and Zhang utilized the higher boiling points of NH 4 F and NH 4 HF 2 (260 and 239.5 °C, respectively) instead of traditional acids to increase the digestion temperatures, successfully determining trace elements in felsic igneous rocks containing the refractory mineral zircon. Later, a PTFE beaker withstanding 300 °C shortened evaporation times in this method and achieved complete digestion of acid-resistant Ti-rich minerals . However, this method faces the risk of incomplete dissolution of chromite-rich rocks …”
Section: Introductionmentioning
confidence: 99%
“…Later, a PTFE beaker withstanding 300 °C shortened evaporation times in this method 9 and achieved complete digestion of acid-resistant Ti-rich minerals. 10 However, this method faces the risk of incomplete dissolution of chromite-rich rocks. 11 Bomb digestion is currently used in most geological laboratories to ensure complete digestion of acid-resistant minerals.…”
Section: ■ Introductionmentioning
confidence: 99%